The believer's authority : what you didn't learn in church - Wommack, Andrew (Tulsa, Okla. : Harrison House, 2009)
Digging into the Scriptures, Andrew reveals the spiritual significance of choices, words, and actions and how they affect a believer's ability to stand against the attacks of Satan and to receive God's best. Discover how the enemy works through your thoughts, interjecting his negative influence on a consistent basis. The devil can't control you outside of your will, but he can use the power of fear, jealousy, envy, bitterness, self-pity and more. A believer's lack of awareness and understanding of the battle only works to the enemy's advantage. By believing God's Word and recognizing what's happening in the spirit realm, you can begin to take the proper action to improve your situation. Learn to release God's power of blessing instead of yielding to Satan's power of sin and death.
Includes bibliographical references (pages 241-242).
Keywords: Authority -- Religious aspects -- Christianity; Spiritual warfare